Comparison of Electron Beam Attenuation in Samples of ABS and HIPS Plastics by Fused Deposition Modeling - Cherepennikov Yu. M. Yuriy Mihaylovich; Miloichikova I. A. Irina Alekseevna; Krasnykh A. A. Angelina Aleksandrovna; Stuchebrov S. G. Sergey Gennadevich (2018, 2018)
Title screen